Respuesta :
[tex]\displaystyle \left \{ {{y=-3x+5} \atop {y=3x-7}} \right. \Rightarrow \left \{ {{y+3x=5} \atop {y-3x=-7}} \right. \\ ~~~~~~~~~~~~~~~~~~~~~~~~~~~~2y/=-2 \Rightarrow y=- \frac{2}{2} \Rightarrow y=-1 \\ y+3x=5 \\ -1+3x=5 \\ 3x=5+1 \\ 2x=6 \\ x= \frac{6}{2} \\ x=3 [/tex]
y = -3x + 5
y = 3x - 7
-3x + 5 = 3x - 7
+ 3x + 3x
5 = 6x - 7
+ 7 + 7
12 = 6x
6 6
2 = x
y = -3x + 5
y = -3(2) + 5
y = -6 + 5
y = -1
(x, y) = (2, -1)
y = 3x - 7
-3x + 5 = 3x - 7
+ 3x + 3x
5 = 6x - 7
+ 7 + 7
12 = 6x
6 6
2 = x
y = -3x + 5
y = -3(2) + 5
y = -6 + 5
y = -1
(x, y) = (2, -1)